PREPARATION OF LIQUID HIDROCARBON FUEL BY CRACKING - Agus Sundaryono dan Budiyanto (Department of Agroindustrial Technology, Bogor Agricultural University, 2010)
ABSTRACT The objective of the study was to evaluate the utilization of two types of zeolite catalists to produce liquid hidrocarbon fuel from oil fraction of palm oil mill effluent (POME). The oil fractions of POME were converted into metil ester prior to be cracked using bifunctional catalist of zeolite. Esterification of the oil was done by using H2SO4 at 60 oC for two hours and transesterification of it by using NaOH at 55 oC. The product methtyl ester of the POME was cracked with zeolit catalists Cr-H-ZA (25:1) and Ni-H-ZA. The result had indicated that zeolit catalist Cr-H-ZA could yield liquid hidrocarbon that containing fraction of gasoline fuel better than zeolite catalist Ni-H-ZA. The product liquid hidrocarbon had kinematic viscosity of 0.8329 cSt and had similar properties of gasoline fuel. Keywords: catalitic craking, liquid hidrocarbon fuel, methylester, POME